Human resource development strategy model: a case study on small and medium Laweyan Batik industry in Surakarta - Agus Utomo; Yosephine Angelina Yulia (Journal of Economics, Business, and Accountancy Ventura, 2018)
Batik industry in Indonesia is generally small and medium enterprises (SMEs) become the livelihood of some people. In the History of Solo Batik describes the famous solo batik with traditional patterns and patterns of batik in the process of cap and in batik tulis. Kampung Batik Laweyan is the center of the township of batik entrepreneurs in Solo, which has tremendous appeal. The lack of regeneration of batik makers makes their numbers more and more decreasing. In order for batik existence to stay awake in the future, business managers must know how to develop human resources especially for batik crafters. The purpose of this research is to formulate human resource development strategy / method used this research is qualitative method with method soft system methodology (SSM) developed by Checkland and Poulter (2010), Checkland and Scholes (1990). The findings obtained after using the method of soft system methodology (SSM) is the formulation of human resources development strategy for medium and small industries in Laweyan, Surakarta.